The Interaction of the Kemambang Village Community in Developing a Tourist Village - Puri Kusuma Dwi Putri; Zahrotul Umami; Devi Purnamasari (Yayasan Ilomata, 2022)
Kemambang Village is located in Banyubiru district, Semarang Regency, Ambarawa, with natural potential (natural scenery, dispensary plantations, coffee plantations, and so on); culinary potential (Kumambang mas coffee, Jamu, Gula Ant, and so on); and cultural potential (Rodat dance, Keprajurita dance, Merti Desa, and so on). Kemambang shows that the potential of villages is very diverse, but villages have not been able to optimize the potential of existing resources due to lack of knowledge of Human Resources (HR) and infrastructure. This study aims to determine the interaction of the kemambang village community in developing tourist villages. The theory used in this study is ecological communication popularized by Luhman (1989). Luhman uses the concept of